Role of School Culture in Enhancing Students’ Learning Character at MA Madrasatul Qur’aniyah - Azhari, Anderian; Rahmadi, Didin Septa; Ningsih, Dewi Puspita; Hilmi, Muhammad Zoher (Primary Journal of Multidisciplinary Research, 2025)
This study aims to examine the role of school culture in enhancing students’ learning character at MA Madrasatul Qur’aniyah. Employing a qualitative approach with a case study method, the research involved in-depth interviews with the principal, teachers, and students as key informants. The findings indicate that a consistent and religiously oriented school culture—such as Qur’an recitation, greeting teachers respectfully, and congregational prayers—significantly shapes students’ learning character. Furthermore, teachers’ role modeling emerges as a critical factor, as students tend to emulate positive behaviors demonstrated by teachers, including discipline, honesty, responsibility, and politeness. Supporting factors include the principal’s encouragement and the systematic habituation of positive practices. Meanwhile, challenges encountered comprise students’ lack of self-awareness, negative peer influence, entrenched bad habits, and external factors such as excessive gadget use and limited family support. Overall, the study underscores that the synergy between a strong school culture, teacher role models, and student motivation is key to fostering positive learning character. The findings have implications for developing character-based educational strategies in religious secondary schools and can serve as a reference for educators seeking to create a conducive learning environment